Obstetrical Factors in Postpartum Depression: A Correlational Study at General Hospitals of Banjarmasin - Winda Ayu Fazraningtyas; Anggrita Sari; Dini Rahmayani (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Problematic health areas such as maternal and child health is one of the target areas to be addressed so that by 2030, reduction of maternal mortality by less than 70 per 100,000 live births will be attained. Mental illness that happens in postpartum women is significantly associated with morbidity and disability. There are about 10% of pregnant women and 13% of mothers who experience mental disorder, especially depression worldwide. This study aimed to determine and analyze the obstetrical factors associated with postpartum depression. This study used quantitative design with descriptive survey method. A total of 88 participants were included coming from the two General Hospital in Banjarmasin, South Kalimantan, Indonesia. EPDS, BDI-II, and PPDRF checklist were used. It was found out that there is no significant association between the level of depression and desire to be pregnant, complication in pregnancy, and history of abortion. However, there is a significant relationship between participants’ level of depression and their experience of menstrual problems. There are 15 or 17% mothers who suffered severe postpartum depression in both hospitals. This needs to be a concern for health workers because postpartum depression mothers could have a poor relationship with children, difficulty meeting their daily needs, caring for children, or even developing into postpartum psychosis.